2018
DOI: 10.21926/obm.icm.1901019
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Electrodermal Activity on Acupuncture Points of Lymphatic, Lung, Nervous, Endocrine and Heart Meridians after Running Exercise, a Single Case Study

Abstract: Background: Electrodermal measurement of acupuncture points has been correlated to physiologic and pathologic conditions with clinical and laboratory studies. Emerging evidence indicates that in addition to therapeutic effect, acupuncture points may also have diagnostic properties. However, physiologic basis of this phenomenon is still unknown. Objective: To determine how electrodermal activity of acupuncture points on hands and feet responds to exercise-induced sympathetic stress and how electrodermal measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Studies on electrodermal measurement of acupoints have shown a relationship between changes in acupuncture point electrical impedance and several clinical conditions and that experimentally induced physiological stress and subsequent recovery correlate with changes in acupuncture point electrical activity [18,19].Electrodermal impedance measurement was used to screen various conditions, including cystic fibrosis, chronic pelvic pain, lung cancer, gastrointestinal bleeding, and assessment of a person's emotional state [20][21][22][23][24][25]. The correlation between changes in the electrodermal activity of APs and respiratory conditions and the electrodermal activity of APs of different meridians of the EAV diagnosis with running exercise has been demonstrated [10,26]. The results of a non-invasive MT method for determining the daily doses of sofosbuvir in patients with chronic hepatitis C infection are described [8].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on electrodermal measurement of acupoints have shown a relationship between changes in acupuncture point electrical impedance and several clinical conditions and that experimentally induced physiological stress and subsequent recovery correlate with changes in acupuncture point electrical activity [18,19].Electrodermal impedance measurement was used to screen various conditions, including cystic fibrosis, chronic pelvic pain, lung cancer, gastrointestinal bleeding, and assessment of a person's emotional state [20][21][22][23][24][25]. The correlation between changes in the electrodermal activity of APs and respiratory conditions and the electrodermal activity of APs of different meridians of the EAV diagnosis with running exercise has been demonstrated [10,26]. The results of a non-invasive MT method for determining the daily doses of sofosbuvir in patients with chronic hepatitis C infection are described [8].…”
Section: Discussionmentioning
confidence: 99%